Attitudes about the treatment of obesity among healthcare providers involved in the care of obesity‐related diseases: A survey across medical specialties in multiple European countries - Francesco Rubino; Jennifer Logue; Mette Bøgelund; Maria Elmegaard Madsen; Ana‐Paula Cancino; Maria Høy; Ulrik Haagen Panton (Wiley, 2021)
Abstract Background and rationale Obesity is associated with the development and progression of many diseases. Understanding and management of obesity have become increasingly important; however, a knowledge gap remains between how healthcare providers (HCPs) consider weight‐loss treatment and the importance of weight loss for improving obesity‐related diseases. Objective The objective of this study was to investigate how HCPs assess obesity, how they interpret the relationship between obesity and 12 recognized co‐morbidities of obesity (excluding diabetes), and their view about the value of various weight‐loss therapies. Methods This was a cross‐sectional, non‐interventional, descriptive study. Participants were medical doctors (HCPs) from eight European countries. Results Eighty‐nine percent of the 197 HCPs that completed the survey considered obesity a disease. For most of the 12 obesity‐related diseases under consideration, a majority of HCPs agreed that weight loss could reverse the disease or prevent progression. Among HCPs who have recommended weight loss, lifestyle interventions were by far the most common recommendation. However, more than three out of four HCPs stated that they would be likely to prescribe anti‐obesity medications if available and reimbursed. Conclusion Most HCPs in this survey consider obesity a disease that needs to be treated. However, the majority of HCPs appear to prefer recommending lifestyle changes, although it is well documented that weight loss obtained by lifestyle changes is difficult to maintain. These results underscore the need for improved education of HCPs involved in the treatment of obesity‐related diseases.